Financial Fraud Study on Weaknesses in Standard Operational Procedures for Procurement of Goods and Services (Case Study of PT SDI) - Pandu Kurniawan; Lela Angraeni (Eduvest - Journal of Universal Studies, 2025)
Implementation of Agreed-upon Procedures (AUP) carried out by KAP Adi and Deki in detecting fraud in the PT SDI goods and services procurement process, there were several shortcomings and obstacles that occurred, including the implementation time exceeding the target so that the implementation process was not optimal. The aim of this research is to evaluate the results of the implementation of Agreed-upon Procedures by KAP Adi and Deki, to prepare recommendations for Standard Operating Procedures (SOP) for implementing procedures. Without clear SOPs, consistency, compliance and efficiency in audit implementation can be disrupted. Therefore, the existence of this SOP recommendation can help the implementation of the Agreed-upon Procedure carried out by KAP Adi and Deki so that it can run effectively and in accordance with applicable standards, namely Related Service Standards (SJT) 4400, namely International Standard on Related Services (ISRS) 4400.